2013
DOI: 10.1099/jmm.0.050492-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and resistance mechanisms of imipenem-non-susceptible Klebsiella pneumoniae in Taiwan: results from the Taiwan surveillance of antibiotic resistance (TSAR) study, 2002–2009

Abstract: We investigated the molecular mechanisms and clonality of imipenem-non-susceptible Klebsiella pneumoniae isolates collected during a Taiwan national surveillance programme, between 2002 and 2009. Genes for carbapenemases, plasmid-borne ampC-type genes and extended-spectrum b-lactamase (ESBL) genes were analysed by PCR. The major porin channels OmpK35 and OmpK36 were studied by SDS-PAGE. Molecular typing was performed with pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST). Our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…2,17,18 Specific capsular serotypes have been documented with a high frequency to show hyper-virulence in mouse and human infections. 19 A cluster of genes are involved in capsule synthesis and driven by 2 promotors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,17,18 Specific capsular serotypes have been documented with a high frequency to show hyper-virulence in mouse and human infections. 19 A cluster of genes are involved in capsule synthesis and driven by 2 promotors.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,11 Construction of in-frame deletion mutants in Serotype K20 and CPS gene exchange from serotype K1 to K20…”
Section: Detection Of Virulence Determinants For Hypervirulent Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Detection of carbapenemases (bla KPC , bla NDM , bla VIM , bla IMP , bla NMC , bla SME , bla SPM-1 , bla GIM-1 , bla SIM-1 , bla IMI , bla GES , and bla OXA-48 ) and extendedspectrum ␤-lactamases (ESBLs) and AmpC genes (bla SHV , bla TEM , bla DHA , bla CMY , bla CTX-M-G1 , bla CTX-M-G2 , and bla CTX-M-G9 ) was performed, and only bla IMP-8 was found in these two isolates (8,9). Both isolates contained two plasmids (ca.…”
mentioning
confidence: 99%
“…The strain was phenotypically confirmed as an ESBL producer, and screening of ␤-lactamase genes with PCR and sequencing showed that it carried bla CTX-M-15 as well as bla SHV-1 and bla OXA-1 . Multilocus sequence typing (www.pasteur.fr/mlst) (5) assigned the strain to sequence type (ST) 48, an ST which has been reported in association with ESBL production worldwide (6)(7)(8)(9)(10). Given the resistance phenotype consistent with 16S RMTase production, the strain was screened for 16S RMTase genes using PCR (2,11,12).…”
Section: Figmentioning
confidence: 99%